O programa do leite e as estratégias de fortalecimento da pecuária leiteira e (re)produção da agricultura familiar camponesa no município de Cabaceiras (PB) - Silva, Suayze Douglas da (2018)
The present study aims to understand the “Milk Program” as a strategy to strengthen dairy farming and (re)production of peasant family agriculture in Cabaceiras (PB), a municipality located in the Microregion of Eastern Cariri in the state of Paraíba. The social problems in the study area are more intense/evident in the period of prolonged droughts, since the phenomenon of drought imposes certain restrictions on the productive system, related to the activities of the primary sector. However, this situation has been changed through the implementation of public policies that foster the development of peasant family agriculture, an activity found in a territory permeated by social relations of power. In this process, the Milk Program, a public policy that integrates the “Food Acquisition Programme”, plays an important role in that it absorbs part of the dairy production of peasant family agriculture, and then destines it to school meals. The Milk Program, created in the first year of Luiz Inácio Lula da Silva’s first term, seeks to ensure the free distribution of milk in order to combat the malnutrition of the population, thereby improving the quality of their lives through milk consumption. In regard to the method, we highlight the following procedures: bibliographic survey, collection of secondary data and fieldwork. Dialectical and historical materialism was used as a reference for the analysis and understanding of socio-territorial dynamics in the study area. In this sense, it was found that the Milk Program is contributing to the improvement of the living conditions of the poorest families, since it is generating and improving income, as well as promoting the social reproduction of peasant family farmers. Despite the improvements highlighted by the social actors with whom we have been in contact, there are still many issues that prevent their reproduction, such as the bureaucratization of the program and the dependence of peasant family farmers on the state, considering the quota of milk supply determined by the program. In this way, we understand that a portion of the population living in the study area still presents lack of opportunities and freedom, indispensable conditions for a full social development.